KINERJA LALU LINTAS PADA RUAS JALAN SATU ARAH (STUDI KASUS JL. SUNAN KUDUS KABUPATEN KUDUS) - Paripurna, Drian; Supriyanto, Joko; Rizani, Mohammad Debby; Yudaningrum, Farida (Jurnal Teknik Sipil Giratory UPGRIS, 2025)
The high mobility of the people and traffic due to the existence of a railroad crossing on the Mranggen road section is the main factor for the high congestion that exists on this section. The government's efforts through the Central Java Office of Public Works and Human Settlements to build the Ganefo Mranggen KM 14 Fly Over is an alternative solution to tackling the high traffic jams on this section. Therefore, researchers will identify how the performance of the Mranggen road section after the construction of the Fly Over. After conducting research, it was found that the busiest traffic was on Wednesday at 16.00-16.15 with a total flow value of 883.3 pcu/hour. The degree of saturation is 0.962 0.75, which exceeds the requirements of the 1997 MKJI guidelines. If the value of the degree of saturation 0.75 requires improvement, then the degree of saturation is included in the category E service level with conditions of very high traffic density and low volume. The highest side resistance value on this section is 906.8 where the time interval is 06.00-09.00 WIB with the VH Resistance Class (906.8 900) which means commercial area, with roadside market activity. So that alternative solutions can be found using SWOT calculations where it is known that the segment is in a position between the Weakness and Opportunity axes, namely in quadrant 4. This means that the Ganefo Mranggen Fly Over segment is advised to change the strategy from internal Weaknesses So that the strategy is changed to Opportunity ( external Opportunity) in order to achieve good traffic performance on the Ganefo Mranggen Km 14 Fly Over section.